Pengaruh Experiental Marketing dan Inovasi Produk terhadap Loyalitas Pelanggan Kedai D’bago Cijeruk melalui Intervening Kepuasan Pelanggan - Hamdani, Dede; Andari, Titiek Tjahja; Yulianingsih, Yulianingsih (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the effect of experiential marketing and product innovation on customer loyalty at D'Bago Cijeruk shop with customer satisfaction as an intervening variable. Customer loyalty is an important aspect for business continuity and growth, especially in the competitive food and beverage industry. Through a quantitative approach, data was collected using a questionnaire distributed to 100 respondents who were customers of Kedai D'Bago Cijeruk.The results of the analysis show that experiential marketing and product innovation have a positive and significant influence on customer satisfaction. In addition, customer satisfaction is also proven to have a positive effect on customer loyalty. This study concludes that the positive experiences gained by customers through experiential marketing and product innovation can increase satisfaction, which in turn increases customer loyalty. Therefore, D'Bago Cijeruk shop is advised to continue to improve experiential marketing strategies and innovate products to maintain and increase customer loyalty.